2018
DOI: 10.1016/j.ophtha.2017.12.039
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Adalimumab in Patients with Noninfectious Uveitis in an Ongoing Open-Label Study: VISUAL III

Abstract: Patients with active uveitis at study entry who received adalimumab therapy were likely to achieve quiescence, improve visual acuity, and reduce their daily uveitis-related systemic corticosteroid use. Most patients with inactive uveitis at study entry sustained quiescence without a systemic corticosteroid dose increase. No new safety signals were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
116
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(130 citation statements)
references
References 35 publications
8
116
0
6
Order By: Relevance
“…There were no new safety signals observed, with the rate of adverse events similar to previously reported studies. A follow‐up trial showed that patients with active uveitis who received adalimumab were likely to achieve disease quiescence, improvement in visual acuity and reduce their systemic corticosteroid use, consistent with the results of previous trials …”
Section: Tnf‐α Inhibitorssupporting
confidence: 85%
See 1 more Smart Citation
“…There were no new safety signals observed, with the rate of adverse events similar to previously reported studies. A follow‐up trial showed that patients with active uveitis who received adalimumab were likely to achieve disease quiescence, improvement in visual acuity and reduce their systemic corticosteroid use, consistent with the results of previous trials …”
Section: Tnf‐α Inhibitorssupporting
confidence: 85%
“…A follow-up trial showed that patients with active uveitis who received adalimumab were likely to achieve disease quiescence, improvement in visual acuity and reduce their systemic corticosteroid use, consistent with the results of previous trials. 53 Though they are both TNF-α inhibitors, adalimumab has some preliminary advantages over infliximab. First, adalimumab offers greater patient independence due to its subcutaneous (s.c.) route of administration, allowing patients the option of self-injection that does not require hospitalisation, thereby increasing compliance and reducing institution costs.…”
Section: Adalimumabmentioning
confidence: 99%
“…Preliminary data are available from a conference abstract. 91 This states that, of 243 patients with active uveitis after 78 weeks, 96.3% had no new inflammatory lesions relative to week 8, 91.0% had an AC cell grade of ≤ 0.5+ and 87.8% had a VH grade of ≤ 0.5+. Of 128 patients with inactive uveitis after 54 weeks, 98.5% had no new inflammatory lesions relative to baseline, 98.5% had an AC cell grade of ≤ 0.5+ and 92.6% had a VH grade of ≤ 0.5+.…”
Section: Ongoing Studiesmentioning
confidence: 97%
“…The median time to treatment failure was also significantly higher in the adalimumab group (>18 months) compared to 8.3 months of the placebo group ( P < .05). The patients who completed VISUAL I and II with and without treatment failure were given an option to enrol into the open‐label extension study for these trials, namely VISUAL III . All the patients in VISUAL III received 40 mg subcutaneous adalimumab every other week.…”
Section: Current Therapiesmentioning
confidence: 99%
“…The patients who completed VISUAL I and II with and without treatment failure were given an option to enrol into the open-label extension study for these trials, namely VISUAL III. 97 All the patients in VISUAL III received 40 mg subcutaneous adalimumab every other week. The interim results at week 70 demonstrate that 60% of the patients with active uveitis had achieved quiescence, whereas 74% of the patients who had inactive disease remained inactive with most of them not needing any systemic corticosteroids.…”
Section: Adalimumabmentioning
confidence: 99%